OC-033 Is Lymphocytic Duodenosis a Marker for Irritable Bowel Syndrome?. (4th June 2013) - Aziz, I; Smillie, D M; Sanders, D S
Abstract : Introduction: Lymphocytic duodenosis (LD) is defined by normal villous architecture and intraepithelial lymphocytes (IELs) > 25 per 100 enterocytes. Such patients should not be diagnosed with coeliac disease (CD), solely by histology, as recent studies have suggested other associations with LD. Despite a paucity of data, previous investigators have suggested that LD may also be associated with irritable bowel syndrome (IBS). Aims To prospectively assess the associations between LD and IBS. Methods: Two hundred patients with LD were investigated for associated LD conditions, by means of revisiting the patient's history and recent investigations including the initial coeliac serology, followed by a combination of gluten challenge, HLA typing, repeat duodenal biopsies, and exclusion of infection/inflammatory bowel disease. A diagnosis of CD was based on the persistence or progression of LD on a gluten-containing diet, the presence of HLA DQ2 or DQ8, and a clinical response to a gluten free diet. In the absence of an alternative cause, a diagnosis of IBS was made on the presence of the ROME III criteria. Results: 150 female, 50 male, mean age 49, SD 16, age range 17–83 An identifiable association was found in 70% of patients : CD (20%), NSAIDs (17%) and H.pylori (16%) accounting for the majority. Other causes included gastrointestinal infections (7%), autoimmune disorders (5.5%), inflammatory bowel disease (2%), TB or HIV (1.5%), and IgA deficiency (1%). In 60 cases (30%) no cause was found, although reassuringly two-thirds normalised their histology. In just over half of those without an identifiable cause, symptoms were consistent with IBS (35/60). IBS, therefore, accounted for 17% of all LD cases. Whereas all patients with CD were HLA positive, only 55% of those with alternative causes or IBS were HLA positive (p < 0.0001). Conclusion: 17% of LD is associated with the Rome III criteria for IBS. LD may, therefore, be a disease marker for IBS and a reflection of low grade inflammatory response although no clues to the triggering mechanism were elucidated. Disclosure of Interest: None Declared